2020
DOI: 10.1371/journal.pone.0231743
|View full text |Cite|
|
Sign up to set email alerts
|

Variability in engagement and progress in efficacious integrated collaborative care for primary care patients with obesity and depression: Within-treatment analysis in the RAINBOW trial

Abstract: Introduction The RAINBOW randomized clinical trial validated the efficacy of an integrated collaborative care intervention for obesity and depression in primary care, although the effect was modest. To inform intervention optimization, this study investigated within-treatment variability in participant engagement and progress. Methods Data were collected in 2014-2017 and analyzed post hoc in 2018. Cluster analysis evaluated patterns of change in weekly self-monitored weight from week 6 up to week 52 and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Thus, the questions of whether the findings are specific to this highly vulnerable population, as well as refinements to the precision of our effect size estimates, some of which are smaller might have been anticipated based on prior literature, will require further investigation. In the parent RAINBOW trial, the range of response differed markedly [44] as is also the case for pharmacotherapy trials, indicating that a more stratified, personalized approach focused on subgroups could be of value. In the parent RAINBOW trial, the range of response differed markedly [41] as is also the case for pharmacotherapy trials, indicating that a more stratified, personalized approach focused on subgroups could be of value.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the questions of whether the findings are specific to this highly vulnerable population, as well as refinements to the precision of our effect size estimates, some of which are smaller might have been anticipated based on prior literature, will require further investigation. In the parent RAINBOW trial, the range of response differed markedly [44] as is also the case for pharmacotherapy trials, indicating that a more stratified, personalized approach focused on subgroups could be of value. In the parent RAINBOW trial, the range of response differed markedly [41] as is also the case for pharmacotherapy trials, indicating that a more stratified, personalized approach focused on subgroups could be of value.…”
Section: Discussionmentioning
confidence: 91%
“…For example, the main outcomes analysis revealed that 73.5% of intervention participants completed at least 7 of the 9 intensive treatment sessions, and 64.7% completed at least 5 of the 6 maintenance sessions [ 6 ]. Further, a priori secondary analyses revealed that (a) lifestyle and cognitive factors did not significantly mediate the main treatment effects as predicted [ 14 ], (b) sex significantly moderated treatment effects for both depression and weight, with males achieving greater reductions in BMI across multiple study time points and females achieving better depression at the 12-month timepoint [ 15 ], and (c) within-treatment analyses showed that poor engagement early in the intervention predicted treatment failure at the end of the intervention [ 16 ]. Future adaptations of I-CARE that increase the tailoring and targeting of intervention components to participants’ stated needs could also increase adherence and potentially enhance lifestyle and cognitive factors that mediate treatment effects by making I-CARE more engaging, thereby increasing effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the potential weight loss effectiveness of a collaborative care approach to obesity treatment (Ma et al, 2019;Lv et al, 2020). Prior work testing a collaborative care approach for patients with depression and obesity demonstrated modest weight loss at 12 months, though the majority of participants did not achieve clinically significant weight loss (Ma et al, 2019;Pagoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%